SAT0395 Sonoelastography detects salivary gland dysfunction in patients with primary sjögren's syndrome. (23rd January 2014) - Dejaco, C.; DeZordo, T.; Heber, D.; Lipp, R.; Lutfi, A.; Magyar, M.; Zauner, D.; Graninger, W.B.; Hermann, J.
Abstract : Background: Sialoscintigraphy (Szinti) is used to investigate salivary gland function in patients with primary Sjögren's syndrome (pSS). Real-time sonoelastography (SElasto) indicates tissue rigidity of salivary glands and correlates with an impaired saliva production. Objectives: To investigate the value of SElasto and B-mode sonography to identify pSS patients with dysfunctional salivary glands. Methods: Prospective study on 37 pSS patients fulfilling the American-European consensus group criteria [mean age 59 years; 92% female; median disease duration 3.1 years]. Szinti was conducted according to a routine protocol and semiquantitative scoring was performed (1): each gland was graded into 3= severe dysfunction, 2= moderate dysfunction, 1= mild dysfunction or 0= normal function. B-mode sonography and SElasto of parotid and submandibular glands was performed using a GE Logiq E9 ultrasound device. Parenchymal homogenicity, echogenicity, hypoechogenic areals, hyperechoic reflections and clearness of glandular borders were also semiquantitatively scored (total score 0-48) (2). SElasto was used to examine the elasticity of glandular parenchyma and a semiquantitative rating was performed with 0=no, 1=up to 25%, 2=up to 50%, 3=up to 75% and 4=more than 75% hardened areas within the salivary gland (total score 0-16). Interobserver variability of sonography and Szinti were tested in 30% of pSS patients. Results: The mean Szinti score of pSS patients was 6.0 (±4.3). Loss function of 1, 2 or 4 salivary glands was present in 5.3%, 17.5% and 19.3% of patients, respectively. B-mode (corrcoeff 0.65, p<0.001) as well as SElasto scores (corrcoeff 0.39, p=0.02) correlated with the Szinti score. Patients with at least one dysfunctional salivary gland had higher B-mode [median 27.5 (range 10.0-44.0) vs. 12.0 (2.0-6.9) p<0.001] and SElasto scores [median 7.0 (range 3.0-12.0) vs. 6.0 (2.0-7.0) p=0.032] than patients with normal salivary gland function. In ROC curve analysis we found an area under the curve (AUC) of 0.91 (95%CI 0.8-1.0, p<0.001) and 0.73 (0.56-0.89, p=0.03) for B-mode sonography and SElasto, respectively, to detect patients with salivary gland dysfunction. A good reproducibility of B-mode and SElasto results was found as indicated by an ICC of 0.926 (95%CI 0.565-0.983) and 0.934 (0.787-0.981), respectively. Reproducibility of Szinti results was also good (kappa 0.871). Conclusions: Structural changes and increased rigidity of major salivary glands as demonstrated by B-mode sonography and SElasto, respectively correlates closely withsalivary gland dysfunction in patients with pSS. References: Shizukuishi K, Nagaoka S, Kinno Y, Saito M, Takahashi N, Kawamoto M et al. Scoring analysis of salivary gland scintigraphy in patients with Sjögren's syndrome. Ann Nucl Med 2003;17:627-31. Shizukuishi K, Nagaoka S, Kinno Y, Saito M, Takahashi N, Kawamoto M et al. Ultrasonographic changes of major salivary glands in primary Sjogren's syndrome. Diagnostic value of a novel scoring system. Rheumatology 2005;44:768-72 Disclosure of Interest: None Declared